Knowledge about Austim Spectrum Disorder and Maternal Sef-Efficacy: A Study of Mothers with Autistic Children - Gabriella Diva Wiryani; Rini Hildayani (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Autism Spectrum Disorder can be a challenge for parents, especially mothers. One of the protective factors in parenting is parenting self-efficacy, which is influenced by parenting knowledge. This research was shared in two studies. Study 1 aims to test the reliability and validity of the Self-Efficacy for Parenting Task Index (SEPTI) and Autism Spectrum Knowledge Scale, General Version (ASKS-GV) measuring instruments. Study 2 aimed to examine the role of maternal knowledge about ASD on maternal parental efficacy. The participants were 84 mothers of children with ASD. The results of Study 1 showed that both measurement tools were reliable and valid for use. The results of Study 2 also showed that mothers' knowledge of Autism Spectrum Disorder did not affect mothers' parenting self-efficacy.Gangguan perkembangan ASD dapat menjadi tantangan pengasuhan yang dilakukan orang tua, khususnya Ibu. Salah satu faktor protektif pada pengasuhan orang tua adalah parenting self-efficacy yang dipengaruhi oleh parenting knowledge. Penelitian ini dibagikan dalam dua studi. Studi 1 bertujuan untuk menguji reliabilitas dan validitas alat ukur Self- Efficacy for Parenting Task Index (SEPTI) dan Autism Spectrum Knowledge Scale, General Version (ASKS-GV). Studi 2 bertujuan untuk melihat peran pengetahuan ibu mengenai ASD pada parental-efficacy ibu. Partisipan dari berjumlah 84 partisipan Ibu dengan anak ASD. Hasil Studi 1 menunjukkan bahwa kedua alat ukur tersebut reliabel dan valid untuk digunakan. Hasil Studi 2 juga menunjukkan bahwa pengetahuan Ibu mengenai Autism Spectrum Disorder tidak mempengaruhi parenting self-efficacy Ibu.